Pola Komunikasi Keluarga dalam Penerimaan Diri Perempuan dengan Kehamilan Tidak Diinginkan - Putri, Ananda Safira Riza; Astuti, Sri Wahyuning (Jurnal Pustaka Komunikasi, 2024)
The facts show that Self-Acceptance of Unwanted Pregnancy occurs a lot, especially because sexual relations are increasingly considered normalized by today's teenagers. Among the factors that encourage unwanted pregnancies to occur is communication between the couple and their environment. Therefore, this research aims to determine the Communication Patterns in the Family and Environment in Self-Acceptance of Unwanted Pregnancy Decisions in Premarital Relationships. This research is qualitative research with a phenomological approach. As informants for this research were 3 people who were perpetrators of unwanted pregnancies, 1 person from the perpetrator's family, and 1 child and adolescent psychology counselor in the city of Bandung. The results of the research state that in making decisions in conditions of Unwanted Pregnancy, everything happens in conditions that can cause good or bad thinking. The communication that occurs starts from the woman's side to ask her partner for responsibility and then tells the woman's family. So in this action, there were several different responses that the female perpetrators received from their partners. So with the differences in responses that occur, in the end the decisions and conditions that occur are also different.